(untitled) (Analytic Teaching, 1990)
Introduction: Teacher training is unarguably the single most important element in Philosophy for Children. Because Philosophy for Children is above all else educational reform, the program means nothing if it is not taught well year after year by career teachers in everyday classrooms. For this to come about, training in Philosophy for Children must fit into existing structures of teacher education. In this paper I will argue that making such training conform to current practices in the training of teachers risks weakening long-term implementation and that only a new approach to teacher training in Philosophy for Children can bring about genuine educational reform in the schools.